Climate Variability Regional and Thematic Patterns - Tarhule, Aondover (IntechOpen, 2013)
As societies transition to evidence-based adaptation and management there is increasing recognition of the need for understanding climate change and variability dynamics and impacts at regional levels and for various activities. This book is a contribution toward that goal. Readers interested in climate change management will find detailed discussions of climatic variability dynamics in selected regions as well as new innovative ways of monitoring climate change, assessing climate risks, and predicting impacts. Those interested in refreshing the fundamentals of climate change and climate variability will find a very accessible review of the status of knowledge on the subject, including a balanced interrogation of available evidence. In an attempt to keep the book accessible, every effort was made to minimize technical jargon without compromising scientific accuracy. The result should be useful to researchers, practitioners, and policy makers.